Bullying Involvement and Empathy: Child and Target Characteristics. Issue 2 (26th May 2016) - van Noorden, Tirza H. J.; Cillessen, Antonius H. N.; Haselager, Gerbert J. T.; Lansu, Tessa A. M.; Bukowski, William M.
Abstract: This study investigated how the bullying involvement of a child and a target peer are related to empathy. The role of gender was also considered. We hypothesized that empathy primarily varies depending on the bullying role of the target peer. Participants were 264 7–12‐year‐old children (Mage  = 10.02, SD = 1.00; 50% girls) from 33 classrooms who had been selected based on their bullying involvement (bully, victim, bully/victim, noninvolved) in the classroom. Participants completed a cognitive and affective empathy measure for each selected target classmate. We found no differences in cognitive and affective empathy for all targets combined based on children's own bullying involvement. However, when incorporating the targets' bullying involvement, bullies, victims, and bully/victims showed less empathy for each other than for noninvolved peers. Noninvolved children did not differentiate between bullies, victims and bully/victims. Girls reported more cognitive and affective empathy for girls than boys, whereas boys did not differentiate between girls and boys. The results indicated that children's empathy for peers depends primarily on the characteristics of the peer, such as the peer's bullying role and gender.